Description of a new species of the genus Odontomutilla Ashmead (Hymenoptera: Mutillidae) from India - Das, Dipanwita; Kumar, P. Girish; Bhadra, Kakali (Zootaxa, 2017)
A new species, Odontomutilla paderua Das, Girish Kumar, sp. nov. (India: Andhra Pradesh, Himachal Pradesh), which is related to O. speciosa (Smith, 1855) is described and illustrated. A key to females of Indian species is given.